2020
DOI: 10.1158/2326-6066.cir-19-0398
|View full text |Cite
|
Sign up to set email alerts
|

TCR Repertoire Diversity of Peripheral PD-1+CD8+ T Cells Predicts Clinical Outcomes after Immunotherapy in Patients with Non–Small Cell Lung Cancer

Abstract: T-cell receptor (TCR)-based biomarkers might predict patient response to immune checkpoint blockade (ICB) but need further exploration and validation for that use. We sequenced complementarity-determining region 3 of TCRb chains isolated from PD-1 þ CD8 þ T cells to investigate its value for predicting the response to anti-programmed cell death 1 (PD-1)/PD-ligand 1 (PD-L1) therapy in patients with non-small cell lung cancer (NSCLC). Two independent patient cohorts (cohort A, n ¼ 25; cohort B, n ¼ 15) were used… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
172
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(178 citation statements)
references
References 32 publications
5
172
1
Order By: Relevance
“…This interpretation is supported by the dynamics of peripheral PD-1+/CD8+ TCR repertoire during treatment. In fact, the authors found that TCR clonality of sorted PD-1+/CD8+ T cells positively associated with survival outcomes, that is patients with increased clonality had improved survival outcomes as compared to those with decreased TCR clonality [82]. Overall this study point to the PD-1+/CD8+ T cells as source of predictive biomarkers with clinical utility.…”
Section: Lung Cancermentioning
confidence: 56%
See 1 more Smart Citation
“…This interpretation is supported by the dynamics of peripheral PD-1+/CD8+ TCR repertoire during treatment. In fact, the authors found that TCR clonality of sorted PD-1+/CD8+ T cells positively associated with survival outcomes, that is patients with increased clonality had improved survival outcomes as compared to those with decreased TCR clonality [82]. Overall this study point to the PD-1+/CD8+ T cells as source of predictive biomarkers with clinical utility.…”
Section: Lung Cancermentioning
confidence: 56%
“…The first conflicting results on the prognostic and predictive significance of peripheral TCR diversity and clonality in metastatic melanoma may be due to the existence in the whole TCR repertoire of a large number of non-tumor specific TCRs that dilute tumor neoantigen specific TCRs. Starting from this assumption, Han J. et al thought to focus on PD-1+/CD8+ exhausted T cells [82], since this cell subset seems to include the highest number of cytotoxic T cells specific for neoantigen [95]. They found that pretreatment TCR diversity of sorted peripheral PD-1+/CD8+ T cells predicted clinical response to anti PD-1/PD-L1 CBI in non-small cell lung cancer (NSCLC), since patients with a higher diversity had a significantly longer progression-free and overall survival than those with lower diversity.…”
Section: Lung Cancermentioning
confidence: 99%
“…Patients with high pre-treatment TCR diversity, and reduced diversity post anti-PD-1 treatment in their CD8 + PD-1 + T cell population had longer progression-free survival. Importantly, these associations with treatment outcomes were not observed when TCR sequencing was performed on blood CD8 + T cells ( 66 , 68 ).…”
Section: Nuanced Analysis Of Pd-1 + Blood T Cells mentioning
confidence: 98%
“…It was speculated that having a high TCR clonal diversity could correlate with higher probabilities to establish efficacious anti-tumor immune responses. Consequently, several studies have indeed associated a better response to a more diverse TCR repertoire in peripheral T cells [60][61][62][63].…”
Section: Future Perspectivesmentioning
confidence: 99%